Characteristics of the Hailesitai volcanic province, Inner Mongolia, and inferred magma source and tectonic setting. (20th April 2020) - Lin, Min; Yu, Shengyao; Ma, Changqian; Zhao, Xilin; Li, Yujuan; Yang, Zhong; Wang, Feng
Abstract : The Hailesitai volcanic basin, located in the northern part of Greater Hinggan Mountains, is one of the most important Mesozoic volcanic basins within Inner Mongolia. Systematic field and petrographic study shows that the Hailesitai volcanic basin consists of volcanic rocks of the Baiyin'gaolao Formation, which can be subdivided into two different lithological members that record a nearly complete eruption–sedimentation cycle. Seven types of volcanic facies are identified, delineating 17 V‐level volcanic structures that are controlled by NNE‐trending fractures. U–Pb isotope dating of zircon indicates that volcanism occurred during the Early Cretaceous between 132.8 and 131.5 Ma. The SiO2 of Hailesitai volcanic rocks mostly range from 58.9 to 77.46 wt% (rhyolite to trachyandesite) and belong to the high‐K alkaline series (average value of the K2 O 4.07 wt%). The trace‐element characteristics of the rocks indicate that the magmas were derived from the mantle. ε Nd ( t ) values lie between 3.78 and 3.87, The ε Hf ( t ) values of obsidian and rhyolitic range from 5.53 to 10.83 and 3.95 to 11.82, respectively. T DM2 (Hf) range from 819 to 466 Ma and 657 to 311 Ma, respectively. The Nd isotopic composition of the rocks and the Hf isotopic composition of zircon suggest that the magma was derived from the partial melting of depleted mantle. We suggest that the Hailesitai volcanic rocks formed in a post‐orogenic extensional tectonic setting during closure of the Mongolian–Okhotsk Ocean due to subduction of the western Pacific Plate. The source of the magmas was depleted mantle with a minor contribution from the partial melting of Palaeozoic crustal rocks.